2019
DOI: 10.7454/psr.v6i3.4613
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Stem of Pycnarrhena cauliflora through Apoptosis Induction on Human Breast Cancer Cell Line T47D

Abstract: Cytotoxic activities of extracts of Pycnarrhena cauliflora leaves, stems and roots on some human cancer cells have been known. However, the cytotoxicity of stem of Pycnarrhena cauliflora on human breast cancer cell line T47D through an apoptosis induction has not been proven yet. This study was an effort in understanding the cytotoxic activity of stem of Pycnarrhena cauliflora through apoptosis induction. The crude ethanol extract was partitioned between n-hexane and dichloromethane at pH 3, 7 and 9, which was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Diels. was reported to have antioxidant, 10,11 cytotoxic, 12,13 antibacterial activities. 14 In this study, it was reported that methanolic extracts of the P. cauliflora (Miers.)…”
Section: Discussionmentioning
confidence: 99%
“…Diels. was reported to have antioxidant, 10,11 cytotoxic, 12,13 antibacterial activities. 14 In this study, it was reported that methanolic extracts of the P. cauliflora (Miers.)…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid is widely found in natural ingredients such as fish, mushrooms, algae (spirulina), bekai plants, sengkubak plants so that these natural ingredients can replace MSG sold in the market. In addition, sengkubak leaves have many benefits for human health, such as antioxidants, anticancer, anti-acne and anti-bacterial; this has been reported [11,16,31]. Sengkubak can be used as an alternative to the use of natural flavour enhancers so that the potential of this plant is very large as a natural flavouring in the future [31].…”
Section: Extraction and Analysismentioning
confidence: 99%
“…The bioactive plant content can be obtained through extraction by pulling chemical compounds from within the plant. Several studies have been conducted to determine the bioactive content of sengkubak plants using the maceration method [11,16,31]. Based on this, this study refers to the research above by using the maceration method.…”
Section: Extraction and Analysismentioning
confidence: 99%
See 2 more Smart Citations